ANALISIS AKTIVITAS NELAYAN DITINJAU DARI ASPEK SOSIAL DAN EKONOMI DI DESA BINANGA KARAENG KABUPATEN PINRANG - Muh. Sugeng Rahayu Jafar; Syahrul Djafar; Kasmawati Kasmawati (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2021)
Binanga Karaeng village is located in Pinrang Regency, Indonesia. In the village, the majority of the population works as fishermen. This is due to the huge potential of natural resources. However, this has not guaranteed the welfare of fishermen. The purpose of this study is to conduct an analysis of fishermen's activities in terms of their social and economic aspects. Research is done with descriptive methods. Analysis is done by descriptive methods and social analysis. The results showed that the social condition of the community has not prospered due to consumptive community lifestyles, the existence of price monopolies by traders and low levels of fishermen's human resources education. Variable Gross Tonnage, age, and trip capture that has a significant influence on the income of fishermen Binanga Karaeng Village Pinrang Regency. Based on SWOT analysis, the right strategy to solve socio-economic problems in accordance with swot matrix analysis is the role of extension to conduct participatory counseling, provide grant assistance in the form of fishing facilities and infrastructure, provide training related to science and technology, the role of banking to provide capital access to fishermen both individually, group and cooperative so as to improve welfare. Fishermen in Binanga Karaeng Village.